Alzhemier-s Disease -Pathophysiology and Treatment - ASMA SHAHEDA SHAIK; A. ELAYA RAJA; M.VIJAYALAKSHMI; G.DEVALARAO (International Journal of Pharma and Bio Sciences, 2010)
Alzheimer’s disease is one of a slow dreadful disease which is affecting only from the adulthood upto aged people on nervous systems present in brain. In this present review article, the history, pathology, theories, hypothesis, factors, major symptoms and associated symptoms of this particular disease, stages of the disease, diagnosis and current treatment of the disease have been explained neatly and legibly with proper diagrams which is easy to understand. The legends introduced in this topic are very easy to know the reasons for this disease and how to control from its bad effects is also given. Some essential treatments are revealed here which paves a good way to prevent this dreadful disease and its conditions. Finally a discussion is also given to regulate the proper care giving to the affected people who are basically on humanitarism background.